Digital payment systems in an emerging economy - Romny Ly; Bora Ly (Computers in Human Behavior Reports)
This study investigates the factors influencing the adoption of digital payment systems in Cambodia, employing a quantitative approach with 359 Cambodian participants. The research integrates concepts from the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to explore the relationships between perceived ease of use (PEU), perceived usefulness, public attitudes, perceived behavioral control, financial literacy, and the adoption of digital payment systems. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study identifies a significant positive relationship between PEU and attitudes toward digital payment systems, corroborating the TAM's assertion that ease of use is a crucial determinant in technology acceptance. The findings also highlight the critical role of perceived usefulness, extending its implications to include convenience, security, and transactional efficiency. The study underscores the influence of public attitudes and perceived behavioral control on adopting digital payment systems, particularly in an emerging economy. In addition, it reveals the impact of financial literacy, not only as a determinant of adoption but also as a mediator in the relationship between public attitudes and adoption. Behavioral nudges are also identified as significant influences in this context. The research contributes to understanding digital payment adoption in emerging markets. It provides digital financial technology insights for practitioners, policymakers, and educators.